2020
DOI: 10.1111/jvim.15748
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota in horses with asthma

Abstract: Background Gastrointestinal microbiota can be influenced by several factors, including diet and systemic inflammation, and in turn could act as a modulator of the allergic response. Fecal microbiota of horses with asthma has not been described. Hypothesis/Objectives Analyze the bacterial fecal microbiota of horses with and without asthma under different environment and diet conditions, during both remission and exacerbation. Methods Prospective observational study. Feces from 6 asthmatic and 6 healthy horses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 31 publications
1
25
0
2
Order By: Relevance
“…Results of this study showed Bacteroidetes, Firmicutes, and Fibrobacteres as the most abundant phyla in equine feces. Interestingly, samples collected from the same horses at a different timepoint using Illumina sequencing of the V4 region confirmed Bacteroidetes as the most abundant phylum in that herd [26]. In addition, Fibrobacteres were overestimated by Illumina sequencing with regards to Firmicutes in this study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Results of this study showed Bacteroidetes, Firmicutes, and Fibrobacteres as the most abundant phyla in equine feces. Interestingly, samples collected from the same horses at a different timepoint using Illumina sequencing of the V4 region confirmed Bacteroidetes as the most abundant phylum in that herd [26]. In addition, Fibrobacteres were overestimated by Illumina sequencing with regards to Firmicutes in this study.…”
Section: Discussionmentioning
confidence: 47%
“…Further, Subdivision 5, a genus part of the Verrucomicrobia phylum, was overrepresented in horses before antibiotic administration as well. This bacterium is considered part of the healthy equine gut repertoire [26,32]. Lastly, Paraprevotella was overrepresented in horses after antibiotic administration, but its role is unknown [33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Leclere and Costa [ 17 ] examined the effect of pasture, high-quality and poor-quality hay on healthy horses and horses with asthma. There were 2 genera overrepresented in faeces of the healthy horses maintained on pasture ( Coprococcus and unclassified genus from family Enterobacteriaceae), 4 on good-quality hay ( Denitrobacterium , Cellulosilyticum , unclassified genus belonging to Deltaproteobacteria class and unclassified genus belonging to order Sphingobacteriales), and none on dusty hay.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Leclere and Costa [17] examined the effect of pasture, high-quality and poor-quality hay on healthy horses and horses with asthma. There were 2 genera…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation